War, Marriage Markets, and the Sex Ratio at Birth1. (25th April 2014) - Bethmann, Dirk; Kvasnicka, Michael
Abstract In belligerent countries, male‐to‐female sex ratios at birth increased during and shortly after the two world wars. These rises occurred amidst dramatically changed marriage‐market conditions caused by war‐related declines in adult sex ratios, and still defy explanation. Based on county‐level census data for the German state of Bavaria in the years just before and immediately after World War II, we explore the reduced‐form relationship between changes in marriage‐market tightness (the adult sex ratio) and changes in the offspring sex ratio, and we discuss potential mechanisms that might link the two. Our results suggest that war‐induced shortfalls of men significantly increased the percentage of boys among newborns.